2023
DOI: 10.1063/5.0144721
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the electrical degradation of AlGaN-based UV-C LEDs by combined deep-level optical spectroscopy and TCAD simulations

Abstract: The long-term stability of ultraviolet (UV)-C light-emitting diodes (LEDs) is of major importance for many applications. To improve the understanding in this field, we analyzed the degradation of AlGaN-based UVC LEDs and modeled the variation of electrical characteristics by 2D simulations based on the results of deep-level optical spectroscopy (DLOS). The increase in the forward leakage current observed during ageing was ascribed an increase in trap-assisted tunneling. The analysis of the degradation kinetics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…They attributed the improved lifetime to the low dislocation density with AlN substrates. 148 Roccato et al 149 reported a combined deep level spectroscopy and TCAD simulation study where they identified the traps appearing during aging and then simulated what effect their spatial location would have on the device lifetime kinetics. Three deep trap states at E C −0.94 eV, E C −3.06 eV, and E C −3.52 eV were identified and suggested to be located near the electron blocking layer.…”
Section: Literature Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…They attributed the improved lifetime to the low dislocation density with AlN substrates. 148 Roccato et al 149 reported a combined deep level spectroscopy and TCAD simulation study where they identified the traps appearing during aging and then simulated what effect their spatial location would have on the device lifetime kinetics. Three deep trap states at E C −0.94 eV, E C −3.06 eV, and E C −3.52 eV were identified and suggested to be located near the electron blocking layer.…”
Section: Literature Resultsmentioning
confidence: 99%
“…What is clear from the literature is i. Multiple degradation mechanisms may be present 41,108,109,[142][143][144][145][146][147][148][149][150] ii. Migration of defects already present in the as-grown structure, or created during subsequent operation, can migrate into the active regions.…”
Section: Literature Resultsmentioning
confidence: 99%
See 3 more Smart Citations